ANALISIS PENGARUH PENERAPAN PRINSIP GOOD CORPORATE GOVERNANCE TERHADAP PENGELOLAAN DANA DESA OLEH PEMERINTAH DESA (Studi Kasus Di Desa Panggungasri, Desa Bumiayu, dan Desa Sumberagung Kecamatan Panggungrejo Kabupaten Blitar) - Retno Dwi Wandika; M. Cholid Mawardi; Siti Aminah Anwar (e_Jurnal Ilmiah Riset Akuntansi, 2021)
This study was conducted with aims to analyze the effect of applying the principles of good corporate governance to the management of village funds by the village government. This research uses qualitative research methods with a descriptive approach. This research was conducted in three villages, namely Panggungasri Village, Bumiayu Village, and Sumberagung Villages, Panggungrejo District, Blitar Regency. The resource persons selected in this study were the Village Head, Village Secretary, and Village Treasurer. This research was conducted through interviews and documentation. The results showed that the three villages had implemented the principles of good corporate governance well, but there were still many shortcomings that had to be addressed by the respective village governments. The principles of good corporate governance that have been implemented are the principle of accountability, the principle of responsibility and the principle of fairness. Meanwhile, the principles of transparency and independence have not been maximally applied. In general, the implementation of the principles of good corporate governance has been implemented because the village government has carried out activities in accordance with applicable regulations.  Keyword: Good Corporate Governance, Management of Village Funds, Village Government